1978
DOI: 10.1128/aac.14.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activities of Various 9-Phenanthrenemethanols with Special Attention to WR-122,455 and WR-171,669

Abstract: Pilot appraisals of the activities of 16 specially selected 9-phenanthrenemethanols against acute infections with Plasmodium falciparum in owl monkeys showed that all were more active than the reference compound, 455, the most active derivative, and WR-171,669, ranked sixth, were selected for study in human volunteers. To assist this undertaking, appraisals of both compounds in owl monkeys infected with various strains of P. falciparum were expanded. These assessments showed: (i) that 455 of activities again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…As such, it possesses more structural similarities to mefloquine and quinine than it does to the 4-aminoquinoline antimalarial agents. A number of workers have shown HF to be highly active against both chloroquinesusceptible and -resistant isolates of P. falciparum (10,11,26,32,33). This result is in agreement with the present findings, HF being effective against both isolates, with greater antimalarial activity against the chloroquine-resistant K1 isolate than against the chloroquine-susceptible T9.96 isolate.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…As such, it possesses more structural similarities to mefloquine and quinine than it does to the 4-aminoquinoline antimalarial agents. A number of workers have shown HF to be highly active against both chloroquinesusceptible and -resistant isolates of P. falciparum (10,11,26,32,33). This result is in agreement with the present findings, HF being effective against both isolates, with greater antimalarial activity against the chloroquine-resistant K1 isolate than against the chloroquine-susceptible T9.96 isolate.…”
Section: Resultssupporting
confidence: 83%
“…DISCUSSION HF is a 9-phenanthrenemethanol member of the aminoalcohols (10,26,27). As such, it possesses more structural similarities to mefloquine and quinine than it does to the 4-aminoquinoline antimalarial agents.…”
Section: Resultsmentioning
confidence: 99%
“…Second, WR-172,435 and WR-180,409 effect parasite clearance slightly more rapidly tharr mefloquine (25) and much more rapidly than the two phenanthrenemethanols (26) in the various owl monkey models. Third, there is every reason to believe that the toxicological and pharmacological properties of these 4-pyridinemethanols in humans will be as different from those of the quinolinemethanols and phenanthrenemethanols as the latter are from each other.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these pilot appraisals and a critical comparative study which showed that WR- (25,26). Second, WR-172,435 and WR-180,409 effect parasite clearance slightly more rapidly tharr mefloquine (25) and much more rapidly than the two phenanthrenemethanols (26) in the various owl monkey models.…”
Section: Discussionmentioning
confidence: 99%
“…1 Evaluation of these two agents in human V-olunteers infected with the :ulti-drug resistant strain of P. falciparum showed that while both drugs cured such infections, both evoked gastrointestinal sy4nptcxjs. 2 Data ff-cci another laboratory indicated that the biquinate salt of halofantrine might enhance the bioavailability of this drug.…”
Section: Assess Ient Of the Antimalarial Activity Of Wr 079520ab (Dn:mentioning
confidence: 99%